Словацька національна ідея за часів Революції 1848-1849 рр. - Бевзюк, Є. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2019)
На тлі процесу становлення націй народи, позбавлені імперіями
державності, вимагали перегляду власного статусу, а словаки здійснили
спробу досягти визнання своїх національних та соціальних прав. У змісті
національно-культурної словацької парадигми власний етнічний інтерес
домінував над ідеєю громадянського суспільства. Тому практика словацького руху поступово доповнилася планом утвердити свій етнічний
інтегральний потенціал шляхом його емансипації у рамках монархічної
австрійської системи. В умовах мозаїчної імперської етнічної структури
спроба реалізувати свою національну ідею під час «Весни народів» призвела до закріплення у словаків такої форми суспільної поведінки, яка визначила етнополітичну обережність і світоглядний мімезис словацьких ідеологів.
Відповідно, модернізація національної словацької ідеології продовжувала відчутно залежати як від поширення наднаціональної ідеї «австрійства» з її «єдиним імперським народом», так і від подальшої практики реалізації регіональної ідеологічної конструкції становлення угорської політичної нації. А проте, в ієрархії ціннісних суспільно-політичних
орієнтацій словацьких національних ідеологів періоду революції 1848–1849 рр. верхню сходинку посіла ідея територіальної автономії, а
культурна емансипація та захист мови, як і раніше, залишалися пріоритетними завданнями словацького національно-культурного руху. In the process of forming European nations, peoples that were deprived of
their statehood by the empires, demanded a revision of their status, and the
Slovaks made an attempt to reach recognition of their national and social
rights. In the context of the national-cultural Slovak paradigm, its own ethnic
interest dominated over the idea of civil society. Therefore, the Slovak
movement practice was gradually complemented by the plan to establish its
ethnic integral potential through its emancipation within the framework of the
monarchical Austrian system. Under conditions of a mosaic imperial ethnic
structure, the attempt to realize its national idea during the Spring of Peoples
led to the attachment of such a form of social behavior among the Slovaks,
which determined the ethnopolitical caution and world-view mimesis of the
Slovak ideologists.
Accordingly, the modernization of the national Slovak ideology continued
to depend heavily on the spread of the supranational idea of "Austria" with its
"united imperial people," as well as on the further practice of implementing the
regional ideological construction of the Hungarian political nation’s
formation. At the same time, despite the difference in their integration scale,
the first etatist model was designed for the introduction of Slovaks into
Danube Monarchy, and the second — for the construction of the Hungarian
national state. In general, in the hierarchy of socio-political values of the
Slovak national ideologists during the period of the revolution of 1848–1849,
the idea of territorial autonomy was at the top of the agenda, and cultural
emancipation and language protection continued to be the priority tasks of the
Slovak national-cultural movement.